PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) DISERTAI MEDIA KOMIK BIOLOGI UNTUK MENINGKATAN MINAT BELAJAR SISWA DALAM PELAJARAN BIOLOGI PADA SISWA KELAS VII-A SMP NEGERI 14 SURAKARTA TAHUN PELAJARAN 20 - Jatmiko, Agung; Maridi, Maridi; Ariyanto, Joko (P Biologi FKIP UNS Surakarta, 2013)
ABSTRACT ? The purposes of this research is to increase students interest in Biologu of class VII-A SMP Negeri 14 Surakarta through the implementation of Cooperative Model CIRC (Cooperative Integrated Reading and Composition) with Biological Comic in the subject of Pollution. This research is a Classroom Action Research with 3 cycles of action. Each cycle consisting of 4 phases which is planning, acting, observing, , and reflecting. Observational data obtained from the questionnaire, observation paper, and interview. Data validation is use triangulation method. Technical analysis of data is technical descriptive. Result of this research show that in the first cycle, according to the observation score, the average percentage of students interest in the class is 57,53%, 65,12% in the second cycle (worked up 7,59%), and 83,28% in the third cycle (worked up 18,16%). According to the questionnaire score, the average percentage of students interest in the first cycle is 71,04%, 71,77% in the second cycle (worked up 0,73%), and 73,66% in the third cycle (worked up 1,89%). Result of interview show that students. Hasil wawancara siswa dapat disimpulkan bahwa siswa more pleased and find it easier to learn the lessons of biology. Students are also interested in learning, students also are learning during the action is exciting activities. The conclusion of this research is that the implementation of Cooperative Model CIRC (Cooperative Integrated Reading and Composition) with Biological Comic in the subject of Pollution can increase students interest in Biology of class VII-A SMP Negeri 14 Surakarta class year 2011/2012. Keywords: learning model Cooperative Integrated Reading and Composition, biological comic, students interest